Resiliensi dan Kualitas Hidup pada Penderita Diabetes Mellitus - Dwi Yuniar Ramadhani; Siti Hardiyanti (STIKES Adi Husada, 2026)
Diabetes mellitus is a highly complex health issue. It causes both physical and psychological impairments, thereby hindering resilience and affecting quality of life. This study aims to analyze the relationship between resilience and quality of life in people with diabetes mellitus. The study employed a cross-sectional correlational design with purposive sampling, involving a sample size of 45 participants who met the criteria of being DM patients aged 20–75 years and willing to participate in the study. The Conor Davidson Resilience Scale (CD-RISC) was used to measure resilience, and the Diabetes Quality of Life (DQOL) questionnaire was used to assess quality of life. The statistical test used was the Pearson Product-Moment correlation. The results showed that the proportion of participants with high quality of life in the high-resilience group was 70.6%, compared to 21.4% in the low-resilience group, with a p-value of 0.03. This indicates a significant relationship between resilience and quality of life. Resilience particularly the self-control component needs to be enhanced as an integral part of nursing care and health education, as it plays a major role in achieving a better quality of life for people with diabetes mellitus.